PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP VOLUME PENJUALAN PADA PT CIPTA GROUP KOTA BATAM (Studi Kasus Pada Perumahan Buana Bukit Permata di Batam) - Merliati Marbun; Mira Yona; Yannik Ariyati (BENING, 2016)
The Effect of Promotions And Product Quality to Sales Volume of Batam city (case study on housing buana Bukit Permata in Batam)  This study aims to determine the effect of Promotion And Sales Volume Of Product Quality At PT. Cipta Group Batam. This research was conducted with survey approach that consists of variable Promotion and Product Quality (X), and Volume Sales (Y). To prove the effect of Promotion And Sales Volume Of Product Quality, the authors collected data by distributing questionnaires as many as 100 respondents as samples taken from Bukit Permata Buana housing consumers in Batam which already occupies Bukit Permata Buana housing. Data were collected through questionnaires were processed using the application program Statistical Product and Service Solutions (SPSS) version 20. The results showed that the promotion and quality of products jointly contribute to give a positive and significant impact on sales volume amounted to 25.1%, while the remaining 74.9% is influenced by other factors. Partial regression analysis results indicate that the promotion of individual variables have a positive and significant impact on sales volume, while the variable quality of the products individually does not affect the volume of sales.